2018
DOI: 10.1111/add.14475
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and diabetes risk in a Chinese population: a Mendelian randomization analysis

Abstract: Aim To assess the causality between alcohol intake, diabetes risk and related traits. Design Mendelian randomization (MR) study. Subgroup analysis, standard instrumental variable analysis and local average treatment effect (LATE) methods were applied to assess linear and non-linear causality. Setting China. Participants A total of 4536 participants, including 721 diabetes cases. Findings Carriage of an ALDH2 rs671 A allele reduced alcohol consumption by 44.63% [95% confidence interval (CI) = -49.44%, À39.37%].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 45 publications
11
40
1
Order By: Relevance
“…Also, we found that the individuals with the rs671 A allele had lower Glu levels and lower prevalence of diabetes, though multivariate logistic regression analysis results didn't show that the A allele was significantly protective for diabetes in either males or females. This is similar to a previous Mendelian randomization analysis, which showed that the A allele in males was significantly associated with decreased diabetes risk for both the overall population (OR = 0.716, 95% CI: 0.567-0.904, p = 0.005) and moderate drinkers (OR = 0.564, 95% CI: 0.355-0.894, p = 0.015) [30]. Interestingly, another study found that the individuals with the A allele had a lower incidence of microvascular complications associated with alcohol consumption, but a higher incidence of macrovascular complications irrespective of alcohol consumption [31].…”
Section: Discussionsupporting
confidence: 90%
“…Also, we found that the individuals with the rs671 A allele had lower Glu levels and lower prevalence of diabetes, though multivariate logistic regression analysis results didn't show that the A allele was significantly protective for diabetes in either males or females. This is similar to a previous Mendelian randomization analysis, which showed that the A allele in males was significantly associated with decreased diabetes risk for both the overall population (OR = 0.716, 95% CI: 0.567-0.904, p = 0.005) and moderate drinkers (OR = 0.564, 95% CI: 0.355-0.894, p = 0.015) [30]. Interestingly, another study found that the individuals with the A allele had a lower incidence of microvascular complications associated with alcohol consumption, but a higher incidence of macrovascular complications irrespective of alcohol consumption [31].…”
Section: Discussionsupporting
confidence: 90%
“…binge drinkers). Our results are also limited to UK residents and therefore may vary somewhat in other populations although MR studies to date in other populations including Chinese are largely consistent with our findings [27,28,32,33]. More research is needed on the determination of the causal effects of alcohol consumption in race/ethnic groups other than Europeans and East Asians to determine if effects observed to date generalize to all major race/ethnic groups.…”
Section: Discussionsupporting
confidence: 81%
“…The validity of using ALDH2 rs671 and ADH1B rs1229984 as genetic instruments relied on the critical assumption of relevance and the exclusion restriction (Davies et al, 2018). In our research design, the instrumental relevance was satisfied with a priori given the robust associations previously documented (Yeung et al, 2012;Peng et al, 2019). We confirmed these correlations hold in our sample without and with the adjustments for additional controls.…”
Section: Resultssupporting
confidence: 60%
“…There are several reasons to think pleiotropy is unlikely in our setting. First, Yeung et al (2012) and Peng et al (2019) considered this assumption and provided epidemiological evidence for the credibility of ALDH2 rs671 as IV for alcohol 3 Individual genetic ancestral composition gave the percentage of DNA that comes from different populations by comparing an individual genome to hundreds and thousands people with known ancestry and was calculated by using the ADMIXTURE program. The top four ancestries included in the MR estimation are (from high to low) Northern Han, Southern Han, Mongolian, and Japanese.…”
Section: Resultsmentioning
confidence: 99%